VD_FINDINFO Jug / 2012 / 177 vom 16. März 2012 - VD Tribunal cantonal (2012)
MARQUE DE HAUTE RENOMMÉE, CONCURRENCE DÉLOYALE, RISQUE DE CONFUSION | 2 LCD, 3 al. 1 let. d LCD, 3 al. 1 let. e LCD, 3 al. 1 LPM